Struktur Genetik Populasi Burung Betet Jawa (Psittacula alexandri alexandri) Berdasarkan Sekuen DNA Mitokondria Gen ND2 - Astuti, Dwi (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTThis study was aimed to determine the structure and genetic characteristics of the Javan Parakeets (Psittacula alexandri alexandri) in some populations in Java Island based on ND2 gene sequences. This study used 26 birds composed of 9 birds from Bogor (West Java), 8 birds from Cepu/Blora (Central Java), 5 birds from Yogyakarta (DIY), and 4 birds from Ngawi (East Java). Blood samples were taken from each bird and DNA was extracted, and then a single fragment of ND2 gene was PCR amplified. A totaly of 1020-bp of DNA sequence of all individual birds were analyzed and produced low genetic distance between bird populations: 0.0031 Â± 0.0010 (0.0024 Â± 0.0012 to 0.0058 Â± 0.0022). The highest genetic distances among individual bird were found in the Yogyaâs population followed and were lowest in Cepu/Bloraâs population. There were 16 haplotype sequences (Hpa Hpa1-16) found in 26 birds. There were some identical haplotypes in each population, but each population has different haplotypes from each other. The highest haplotype diversity and nucleotida diversity were found in Yogyaâs and Bogor populations. NJ tree showed that each individual bird clustered together corresponded to the population/progeny.Keywords: Javan Parakeets, Psittacula alexandri alexandri, population, ND2 gene sequence genetic distance, diversity